The finance-innovation nexus : implications for socio-economic development - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2024)
The Finance-Innovation Nexus: Implications for Socio-Economic Development provides up-to-date technical portrayals on the contemporary issues pertinent to the interplay of financial technologies and social development in Emerging Economies. The authors utilise a large variety of data sources and methods for their research. Topics covered in this volume include, CEO characteristics and CSR, green finance and investment in emerging economies, behavioral finance, intellectual capital, MIS, and financial performance, capital structure during COVID-19, the online search volume index, working capital, stock return, and banks' risk taking, as well as social capital. Volume 34 in the series, International Symposia in Economic Theory and Econometrics, is essential reading for anyone interested in financial technologies and social development in emerging economies.